2019
DOI: 10.1155/2019/9471407
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fatal Injuries Resulting from Tractor and High Speed Motorcycle Accidents in Turkey: A Multicenter Study

Abstract: Aim. Injuries are among the main causes of mortality and morbidity all over the world, and effective initial triage of these patients can determine the thin line between death and life. Tractor accidents and related injuries are significant problems particularly in rural areas. However, major trauma classification systems do not include tractor accidents as a criterion for trauma team activation or transportation of the patients to a trauma center. This study evaluated the general characteristics and outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The most common cause of tractorrelated deaths between 1985 and 2010 in Australia was tractor overturning (42%), followed by crushing accidents (29%) (18). Rollover was in charge of over half (54%) of tractor-related deaths in the 11-year period in Virginia (10) Thoracic trauma and spinal injuries are claimed to be significantly higher in tractor accidents (19). Injuries due to the head, chest, and abdominal trauma were the main causes of tractor-related deaths in Portugal (8).…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of tractorrelated deaths between 1985 and 2010 in Australia was tractor overturning (42%), followed by crushing accidents (29%) (18). Rollover was in charge of over half (54%) of tractor-related deaths in the 11-year period in Virginia (10) Thoracic trauma and spinal injuries are claimed to be significantly higher in tractor accidents (19). Injuries due to the head, chest, and abdominal trauma were the main causes of tractor-related deaths in Portugal (8).…”
Section: Discussionmentioning
confidence: 99%
“…median GCS value of 15 and a median RTS value of 12(32,35). In terms of studies examining ISS values following tractor accidents, Cogbill et al reported a mean ISS value of 13.3 in one study and 8.5 in another, Kasar O…”
mentioning
confidence: 99%